Răspuns :
Răspuns:
Explicație pas cu pas:
5)
( a + b ) : 2 = 21,35
a + b = 2 × 21,35
a + b = 42,70 → suma celor doua numere
18,3 + b = 42,70
b = 42,7 - 18,3
b = 24,4 → celalalt numar
________________________
6)
( a + b + c ) : 3 = 7,14 → media aritmetica a trei numere
a + b + c = 3 × 7,14
a + b + c = 21,42 → suma celor trei numere
5.
( a + b ) : 2 = 21, 35
a = 18, 3
( 18, 3 + b ) : 2 = 21, 35
18, 3 + b = 21, 35 × 2
18, 3 + b = 42, 7
b = 42, 7 - 18, 3
b = 24, 4
6.
( a + b + c ) : 3 = 7, 14
a + b + c = 7, 14 × 3
a + b + c = 21, 42
( a + b ) : 2 = 21, 35
a = 18, 3
( 18, 3 + b ) : 2 = 21, 35
18, 3 + b = 21, 35 × 2
18, 3 + b = 42, 7
b = 42, 7 - 18, 3
b = 24, 4
6.
( a + b + c ) : 3 = 7, 14
a + b + c = 7, 14 × 3
a + b + c = 21, 42